2012
DOI: 10.1111/j.1526-4610.2012.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, Headaches, and Cognition

Abstract: Objectives and Background.— The possible effects of migraine on executive abilities remain controversial; hence, we studied inter‐ictal cognitive performance of individuals with migraine and non migraine headaches (NMH) compared with headache free controls. Design and Method.— In a cross‐sectional observational study, taking place in primary care, adults aged 50 or above were evaluated by a neurobehavioral battery including several executive measures. Present history of headache was sought, and migraine was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 74 publications
1
67
1
Order By: Relevance
“…In particular, our results revealed lower scores in the subscales assessing verbal memory, attention, frontal and visuospatial functions, in line with several previous studies [815]. The low score on the memory scale (i.e., poor retrieval abilities) might be ascribed to defective strategic and organizational aspects of learning [9], also in consideration of the lower attentional and executive function scores in MwoA patients compared to HCs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In particular, our results revealed lower scores in the subscales assessing verbal memory, attention, frontal and visuospatial functions, in line with several previous studies [815]. The low score on the memory scale (i.e., poor retrieval abilities) might be ascribed to defective strategic and organizational aspects of learning [9], also in consideration of the lower attentional and executive function scores in MwoA patients compared to HCs.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, some studies did not find any cognitive difference between migraine patients and non-migraine subjects [47]. Conversely, other studies revealed that migraine patients are characterized by a poorer cognitive performance [815] during both interictal [11–13] or ictal [16, 17] phases when compared to HCs. In particular, it has been suggested that migraine patients might show selective defects in executive/attention and visuospatial domains [9, 11, 13–15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some longitudinal studies have suggested fewer dysfunctions in the Mini Mental State Examination (MMSE) and executive functions in migraineurs. In addition, some studies have not found any significant differences in cognitive performance between migraine patients and controls [13]. These inconsistencies could be due to methodological issues including different migraine assessment methods and the program of cognitive assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The visual analog scale (VAS) was used to evaluate the average intensity of headache in the past week. Headache was investigated because severe headache is related to impaired cognitive function [18]. …”
Section: Methodsmentioning
confidence: 99%